Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content: 1. Attitudes of university youth towards emigration in light of the war on Syria Tishreen University students as a model Mrs. Celine J. Shaheen 2. Designing women’s fashion that combines traditional fashion lines in the Kingdom of Saudi Arabia with artistic and contemporary schools Co-Prof. Arwa Daoud Khomayyis 3. Benefiting from the aesthetics of the pop art school in recycling used environmental and artistic materials to produce artistic handicrafts Dr. Nashwa Mohamed Issam Abd El-Aziz, Dr. Rasha Hassan Hosny Salem , Dr. Nagwa Kamel Mohamed Bosila 4. Islamic Waqf in Yemen and its Economic Effects Mrs. Thekra Mohammed Al-Hattami 5. The Implications of the Activating Defense Law No.13 of 1992 on Human Rights in Jordanian Society - The Corona pandemic as a model Dr.Dalal Shawkat Alodainat , Prof. Salim Ahmad Alquisi 6. The Role of the British Advisor Charles Belgrave in the Making of the Modern State of Bahrain (1926 - 1957): A Historical Study Dr. Sharaf Mohamed Ali AlMezaal 7. Role of Family Upbringing in Preparing Girls for the Marital Life Requirements in Contemporary Saudi Society (A study on a sample of newly married women in the Kingdom of Saudi Arabia from the different the western, eastern, southern, and northern regions) Dr. Amani Abdulaziz Afghani